Bridging the Information Gap Between Science and Society: A Solution to Nonpoint Source Contamination?. (27th May 2020) - Nutile, Samuel A; Simpson, Adam M; Solan, Megan E
ABSTRACT: The dissemination of information associated with scientific achievement serves to advance research and guide future experimentation. In the sphere of environmental science, such advancements aim to better characterize harmful chemicals and the factors that influence in situ toxicity, which is central to the protection of the environments upon which humans depend. While some information regarding the dangers associated with common anthropogenic contaminants reaches wider audiences, the nuance of this information is often lost, potentially leading to ineffective solutions, specifically as it relates to nonpoint source contamination. Bridging the divide between scientific research, regulatory implementation, and product innovation is imperative in order to find meaningful and lasting environmental solutions. Road de‐icing salts are applied to impervious surfaces to protect human health and maintain the efficient transportation of goods by roadways during winter months. The toxicity of these salts in freshwater ecosystems is well understood and researched within the scientific community. Tentative regulations and solutions developed to mitigate the environmental damage caused by road de‐icing salts, however, perfectly represent the disconnect between the scientific community and the general public. Here, we use road de‐icing salt as an example of how such a disconnect can manifest in the form of ineffective solutions and regulatory standards, and we present a general framework by which environmental scientists can more effectively bridge the gap between the scientific community and society at large. Integr Environ Assess Manag 2020;16:415–420. © 2020 SETAC KEY POINTS: Effective scientific communication can be used to develop effective solutions to nonpoint source contamination through product innovation. Environmental concerns caused by use of road de‐icing salts represents a source of nonpoint source contamination where regulatory and product solutions have failed to effectively mitigate environmental problems. The manuscript provides a framework for disseminating scientific information learned through primary research to the general public to stimulate grassroots environmentalism as a means of mitigating nonpoint source contamination.